Care and Repair and the Politics of Urban Kindness. (February 2015) - Hall, Tom; Smith, Robin James
This article considers the possibility that small acts of urban care, maintenance and cleaning might make for a good city. This might seem a slim possibility, given the vast sociology of hopelessness to which the contemporary city is home. But it can also be argued that a politics, and a sociology, of hope are best looked for not in big picture or utopian thinking but in the practical instances of everyday care and kindness that are as much a part of the urban everyday as anxiety, insecurity and damage. We explore this possibility through a critical assessment of Nigel Thrift's recent writings on urban repair, drawing (but not reporting) on our own research with street cleaners and outreach workers tasked to look out for the rough sleeping homeless.